2017
DOI: 10.17957/ijab/15.0366
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Potential and Biochemical Analysis of Moringa oleifera Leaves

Abstract: Moringa oleifera is extremely valuable plant which has been widely grown in the tropical and subtropical areas. Four accessions {originated from Faisalabad (M-Fsd), Multan (M-Mln), India (PKM1) and China (M-China)} of M. oleifera were analyzed for total phenolics, superoxide dismutase, peroxidase, catalase, protease, esterase, proteins, ascorbate peroxidase, total antioxidant capacity, malondialdehyde and total oxidant status (TOS) during October(autumn), December (winter), January (winter), February (early sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Among these potential biomarkers, components 14, 33, 55, 74, 79, 30, and 80 were identified or tentatively characterized in M. oleifera leaves for the first time. It has been reported that M. oleifera leaves which originate from China have the maximum antioxidant activity when compared alongside those from Faisalabad, Multan, and India [ 73 ]. As is known, biological activity is caused by the high contents of phytochemicals.…”
Section: Discussionmentioning
confidence: 99%
“…Among these potential biomarkers, components 14, 33, 55, 74, 79, 30, and 80 were identified or tentatively characterized in M. oleifera leaves for the first time. It has been reported that M. oleifera leaves which originate from China have the maximum antioxidant activity when compared alongside those from Faisalabad, Multan, and India [ 73 ]. As is known, biological activity is caused by the high contents of phytochemicals.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, there is an increased interest in natural antioxidants that may be used to oppose free radicals with a view to lower the risk of associated diseases. Such reservoirs of natural antioxidants are different products of plant origin [4,8].…”
Section: Introductionmentioning
confidence: 99%
“…A study by Khalid Rai, Hameed [121] investigate the antioxidant potential of Moringa oleifera extract obtained from Moringa oleifera tree grown on different climatic season namely autumn, winter and spring.…”
Section: Potential Metabolites In Moringa Oleiferamentioning
confidence: 99%